Physiology of asthma and involvement of small airways - Irvin, Charles G. (Henry Stewart Talks, 2013)
Physiology of asthma, a syndrome defined by lung dysfunction, Airflow limitation, Small airways, Reversibility of airflow limitation, Periodicity and variability of airflow limitation, Airways hyperresponsiveness
Updated at 2022/05/16